The effect of degree of curvature and fabric orientation on the impact properties of single and multilayer textile composites. Issue 1 (2nd January 2022) - Irfan, Mohammad; Zahid, Bilal; Sidique, Sheraz Hussain; Jamshaid, Hafsa; Rajput, Abdul Waqar; Hou, Aiqin
Abstract: The usage of textile composites as lightweight gadgets is increasing day by day. The application range varies from personal protective tools to aerospace vehicle parts. However, every specific application demands specific functionality. Anisotropic nature of textile materials makes it possible to design composites in structural as well as non-structural shapes. In this research, single and multilayered textile composites were fabricated by using cotton woven fabric as a reinforcement and unsaturated polyester resin as a polymer. The fabrication was done at different degrees of curvature with different fabric orientations (i.e. the positioning of second and third layer fabric was turned from warp to weft) in multilayered composites to analyze their effect on the impact property of the resultant composite. Falling dart impact test was performed, to measure the impact properties of the samples. The curved specimens had shown higher strength as compared to the flat specimens. Furthermore, the increment in the degree of curvature causes the rise in fractural energy value. The number of layers has a direct effect on impact property as the number increases, the strength also increases. Finally, there was no significant effect of fabric orientation observed in double and triple layered composites. Graphical Abstract: